Emotional Reactions Mediate the Effect of Music Listening on Creative Thinking: Perspective of the Arousal-and-Mood Hypothesis - He, Wu-Jing; Wong, Wan-Chi; Hui, Anna N.-N. (Frontiers in Psychology, 2017)
This study examined the effect of music listening on creative thinking through the lens of the arousal-and-mood hypothesis, which posits that emotional reactions (i.e., arousal and valence) mediate the effect of music listening on cognitive functioning. Participants were randomly assigned to three groups: a positive music group (n = 198), a negative music group (n = 195), and a control group (n = 191). Creative thinking and emotional reactions were assessed with the Test for Creative Thinking-Drawing Production and the Affect Grid, respectively. The results showed that both positively and negatively arousing music enhanced creative thinking. The results further revealed that arousal, regardless of valence, significantly mediated the music-creativity relationship. This study enriches the research on the arousal-and-mood hypothesis by (1) providing direct empirical testing on the mediating roles of emotional reactions; (2) including both positively and negatively arousing music in the study design; and (3) identifying that only arousal, and not valence, was a significant mediator in the music-creativity link.